Zgodovinska nasprotja med različnimi rabami gozdov - Perko, Franc (Gozdarski vestnik, 2017)
This article presents the disagreements occurring through the history on the Slovenian territory at colonization, monopoly over forests and wood for the needs of mines and iron works and forest pasture on the example of afforestation of Karst and mountain pasture in Gorenjska region. Numerous conflict situations concerning a specific forest use are described.
Keywords: forest; gozdovi; colonization; kolonizacija; krčenje gozdov; deforestation; mines; rudniki; iron works; ironworks; fužine; gozdna paša; forest pasture; mountain pasture; planinska paša; Slovenia; Slovenija